2015
DOI: 10.1111/ejn.12998
|View full text |Cite
|
Sign up to set email alerts
|

Threat modulates neural responses to looming visual stimuli

Abstract: word count: 231Threat and Looming Stimuli 2

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
39
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(47 citation statements)
references
References 74 publications
(134 reference statements)
7
39
1
Order By: Relevance
“…Like PPS representations that support non‐defensive behaviors, there is evidence that representations of PPS are flexible in defensive contexts. For example, Vagnoni, Andreanidou, Lourenco, and Longo (), Vagnoni, Lourenco, and Longo (), Vagnoni, Lourenco, and Longo () have reported that looming images of threatening stimuli (i.e., snakes and spiders) were judged as arriving sooner than nonthreatening stimuli (i.e., rabbits and butterflies) on a time‐to‐contact (TTC) task. One interpretation is that this effect could result from participants experiencing larger representations of PPS in the presence of evolutionary threatening animals as compared to nonthreatening animals, leading them to judge the former as making contact with themselves sooner.…”
Section: The Defensive Functionmentioning
confidence: 99%
“…Like PPS representations that support non‐defensive behaviors, there is evidence that representations of PPS are flexible in defensive contexts. For example, Vagnoni, Andreanidou, Lourenco, and Longo (), Vagnoni, Lourenco, and Longo (), Vagnoni, Lourenco, and Longo () have reported that looming images of threatening stimuli (i.e., snakes and spiders) were judged as arriving sooner than nonthreatening stimuli (i.e., rabbits and butterflies) on a time‐to‐contact (TTC) task. One interpretation is that this effect could result from participants experiencing larger representations of PPS in the presence of evolutionary threatening animals as compared to nonthreatening animals, leading them to judge the former as making contact with themselves sooner.…”
Section: The Defensive Functionmentioning
confidence: 99%
“…Stimuli were the same as used in our previous experiments (Vagnoni et al 2012 , 2015 ), namely 160 colour photographs collected from the internet, 40 from each of the four categories (snakes, spiders, butterflies, and rabbits). Images were cropped and resized using Adobe Photoshop CS5 (Adobe Systems, San Jose, CA).…”
Section: Experiments 1: Does Reduced Ability Of Movement Influence Timmentioning
confidence: 99%
“…Although looming has been viewed as a simple optical effect, the semantic content of objects approaching our bodies and our individual differences related to fear modulates our responses. For example, participants underestimate the arrival time of threatening, relative to non-threatening, stimuli (Brendel et al 2012 ; Vagnoni et al 2012 , 2015 ). Moreover, these effects are modulated by the specific fears of observers, with people more fearful of threatening stimuli underestimating more their arrival time (Vagnoni et al 2012 , 2015 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Within this framework, theta oscillations are pronounced ∼300 ms after stimulus onset and associated with episodic memory processes (Klimesch, 1996; Klimesch et al , 1997, 2006). In addition, other research modeled threatening contexts more specifically and found alpha band activity to be modulated by threatening stimuli (Vagnoni et al , 2015) whereas anterior midcingulate cortex theta band activity is associated with the recall of conditioned fear (Mueller et al , 2014). However, theta oscillations are sometimes associated with arousal during anticipation of noxious stimuli (Pape and Pare, 2010) suggesting broader roles of the respective frequency bands.…”
Section: Introductionmentioning
confidence: 99%